Pengaruh Kualitas Sistem, Kualitas Informasi dan Kualitas Layanan Terhadap Kepuasan Pengguna Sistem Informasi Manajemen RS “X” Kota Palopo: The Influence of System Quality, Information Quality and Service Quality on User Satisfaction of the Management Information System RS “X” Palopo City - Novita Sari; Ervianingsih Ervianingsih; Izal Zahran (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The development of information systems and technology, which is currently increasing rapidly, is urgently needed by an organization, company or individual to process and obtain data or information more easily, quickly and accurately.